HUFFMAN BASED LZW LOSSLESS IMAGE COMPRESSION USING RETINEX ALGORITHM - Dr. A.s. Gousia Banu; Amaan Mohammed Mouzzam; Abdul rehaan; Mohammed afhaam ismail; Bilal hussain anwar; Faizan ahmed taj (Utilitas Mathematica, 2025)
image data compression is used in picture compression to reduce the number of bits needed to represent an image compared to its original format. Picture compression tries to get rid of extra and unnecessary image data so that it can be stored and sent more quickly. So, picture compression might make transmission faster and lower network latency. when you choose a lossless compression method, the data stays the same during the process and doesn't lose anything. This work presents a new 3-stage lossless compression method for images called Huffman inspired LZW Lossless Compression of images using the Retinex algorithm. the first thing to do is use Huffman coding to make the picture smaller. the second stage is to use LZW to compress the data and then connect all of the Huffman code words to decode it. In step three, the Retinex algorithm is used at the compressed picture to improve the overall quality and contrast of the image. “You can make MATLAB's compression rate (CR) or mean square error (MSE) better by using this strategy”.